Evaluasi Kapasitas Jalan dan Kinerja Sinyal Lalulintas pada Persimpangan Jalan Sisingamangaraja, Jalan Lintas Sumatera, Jalan Tritura di Kota Medan - Simanjuntak, Edi Join; Mahda, Nuril (Universitas Sulawesi Tenggara, 2025)
The rapid growth of vehicle numbers in urban areas is often not matched by improvements in road infrastructure, leading to congestion and reduced traffic performance. This study aims to evaluate the road capacity and the performance of traffic signals at a signalized intersection in [insert location]. The evaluation is conducted using the Indonesian Highway Capacity Manual (IHCM) 1997, which includes calculations of traffic volume, road capacity, degree of saturation (DS), average delay, and level of service (LOS). The analysis results show that the intersection experiences [low/moderate/high] saturation with a DS value of [value], indicating [condition of the intersection's performance]. The average delay of [value seconds/vehicle] suggests that the signal [operates efficiently/needs timing adjustment]. The obtained level of service is categorized as [LOS A–F], reflecting [traffic performance description]. Based on the evaluation, it is recommended to [adjust signal timing/expand capacity/improve intersection geometry] to enhance traffic efficiency in the study area